Proceedings of the 4th International ICST Conference on Wireless Internet 2008
DOI: 10.4108/icst.wicon2008.4787
|View full text |Cite
|
Sign up to set email alerts
|

Efficient XML Usage within Wireless Sensor Networks

Abstract: Integrating wireless sensor networks in heterogeneous networks is a complex task. A reason is the absence of a standardized data exchange format that is supported in all participating sub networks. XML has evolved to the de facto standard data exchange format between heterogeneous networks and systems. However, XML usage within sensor networks has not been introduced because of the limited hardware resources. In this paper, we introduce XML template objects making XML usage applicable within sensor networks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Design choices are being explored to minimize the cost of providing structured data and functionality description, such as compression and tag compacting techniques [15] and HTTP-based service bindings [26]. In addition, Moritz et al [25] propose adaptations and enhancements to limit the number of exchanged DPWS message for service discovery and meta data exchange.…”
Section: Challenge: Integrating External Sensorsmentioning
confidence: 99%
“…Design choices are being explored to minimize the cost of providing structured data and functionality description, such as compression and tag compacting techniques [15] and HTTP-based service bindings [26]. In addition, Moritz et al [25] propose adaptations and enhancements to limit the number of exchanged DPWS message for service discovery and meta data exchange.…”
Section: Challenge: Integrating External Sensorsmentioning
confidence: 99%
“…For the programming language C, as the main choice of language for sensor network engineering, the XML data binding framework autoXML [15] has been presented. However our previous results in [9] have shown that autoXML is also not applicable for sensor network applications because of a steeply increasing memory demand and instable runtime behaviour.…”
Section: Introductionmentioning
confidence: 96%
“…While the presented work on XML compression was not targeted for sensor network usage, the usage of more structured complex data formats in WSNs was firstly discussed in [8] and [9], where a template-based compression approach is presented. As a result using complex XML data and supporting further XML-based application scenarions and protocols, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the limited hardware resources within sensor networks, XML usage was not fully introduced earlier. But now XML usage in sensor networks is made applicable by introducing the XML template objects in an optimized manner [55]. XML is basically a key feature towards the service-oriented sensor networks and a proper medium to support complex data management and heterogeneous sensor networks.…”
Section: Multiservice Provisioning On Multiple Platformsmentioning
confidence: 99%